Evaluasi Usability dan Perbaikan Desain Antarmuka Pengguna Aplikasi Mobile Library Perpustakaan Kota Malang menggunakan Metode Usability Testing - Aisha Damayanti; Satrio Hadi Wijoyo; Alfi Nur Rusydi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Malang City Library is a public library located in Malang, East Java. To support its infrastructure regarding information and communication systems, this library utilizes mobile library as a media that is used to disseminating hospital-related information to general public. This study is focused to assess the level of usability of Malang City Library mobile library application. The methods that were used in this study are firstly testing the task directly to the user to measure aspects of learnability, efficiency, and errors and distributing the System Usability Scale (SUS) questionnaire to measure aspects of satisfaction. This study involved 30 respondents who were divided into categories of students, university students, and the general public. To analyze the data of the task testing results used success rate matrix to measure the level of learnability and obtained results of 71.4%. The efficiency aspect is measured using a time-based efficiency matrix which then gets a result of 0.0428215 task / s from nine tasks. For aspects of errors measured using the defective rate matrix which then obtained an average of nine tasks of 0.513. The last aspect is satisfaction that was tested using SUS questionnaire and obtained results of 20.67, from these outcomes it is concluded that the satisfaction status of Malang City Library mobile library application is still included in the bad category. In addition, this research also resulted in improvements to the interface design based on the problems found.